CAPACITY ANALYSIS IMPROVEMENT FOR SEAFOOD VALUE-ADDED IN KML PLANT II - Rochiman Danil, Daldi
The demand for value-added seafood products continues to increase every year, this happened because value added seafood is a basic need food that has high nutritional value. PT Kelola Mina Laut (KML) is one of the largest seafood processing companies in Indonesia. One of the factories namely KML Plant II, was built specifically for the production of value-added seafood. The product is distributed in domestic market and is targeted to become market leader in that type. In 2021, KML Plant II had a significant decrease in purchase order (PO) fulfilment. the factory service level decreased from 69% to 58% compared to the previous year. One of causes declined in production is by capacity of production machines that are no longer able to meet the existing demand.